Southeast Asia and the Pacific : - Chand, Attar (Sterling, 1979)
The major aim of this bibliography, though selective, is to list together the most signficant books and periodical articles that appeared during the last thirty years (1947 - 1977) in other to provide a base for futher researches, discussion and comprehensive analysis of the subject.